Efeito da fermentação fúngica no teor de compostos fenólicos em casca de café robusta - Palomino Garcia, Lady Rossana [UNESP]; Del Bianchi, Vanildo Luiz [UNESP] (Univ Estadual Londrina, 2015)
Coffee husk is an abundant by-product generated by the coffee industry and it can be used for the production of-value-added phenolic compounds. Currently, this residue has no commercial use due to the presence of anti-nutritional compounds and it is returned to the soil or burned. The aim of this study was to evaluate the content of phenolic compounds in Robusta coffee husk, the adequacy of this residue as substrate for fermentation processes, as well as evaluating the influence of fungal solid state fermentation to obtain phenolic compounds from this residue. In the present study, the use of different solvents for the extraction of polyphenols was evaluated and the content was found to be in the range of 96.9-159.5 mg of galic acid (GA).g(-1) substrate, depending on the solvent used. The best solvent was acetone, therefore it was selected for extraction. Studies were carried out to evaluate the effect of solid-state fermentation in the release of phenolic compounds, using the filamentous fungi Penicillium purpurogenum. The total phenolic content increased from 159.5 up to 243.2 mg GA.g(-1) substrate as a result the solid-state fermentation.

A casca de café é um subproduto abundante gerado pela indústria cafeeira, que pode ser usado para a produção de compostos fenólicos com alto valor agregado. Na atualidade, este resíduo não possui utilização comercial, devido à presença de compostos antinutricionais e é retornado ao solo ou queimado. O objetivo deste trabalho foi a avaliação do teor de compostos fenólicos na casca de café Robusta, a adequação deste resíduo como substrato para processos fermentativos, assim como, a avaliação da influência da fermentação fúngica em estado sólido na obtenção de compostos fenólicos a partir desse resíduo. Foi estudado o uso de diferentes solventes na extração dos polifenóis. O teor de compostos fenólicos na casca de café variou desde 96,9 até 159,5 mg de ácido gálico (AG)·g-1 substrato dependendo do solvente usado. O melhor solvente foi a acetona portanto, o mesmo foi selecionado para as extrações. Foi avaliado o efeito da fermentação em estado sólido na liberação dos compostos fenólicos, usando o fungo filamentosoPenicillium purpurogenum. O conteúdo de fenólicos totais aumentou de 159,5 até 243,2 mg AG·g-1 substrato por efeito da fermentação em estado sólido.
The effect of fungal fermentation in phenolics content in robusta coffee husk
Keywords: Coffea canephora; Bioactive compounds; Solid state fermentation; Penicillium purpurogenum; Coffea canephora; Compostos bioativos; Fermentação em estado sólido; Penicillium purpurogenum.